Wernekink commissure syndrome as the presenting feature in multiple sclerosis - Sasikumar, Sheetal; T J, Jeethu; Alvis Shaji, Chris; Sasidharan, Aswathy (Nepal Journal of Neuroscience, 2024)
Wernekink commissure syndrome is a rare syndrome characterized by bilateral cerebellar signs, internuclear ophthalmoplegia and delayed palatal myoclonus, due to involvement of the caudal paramedian midbrain. It has been almost exclusively described in strokes involving the midbrain. We hereby report the case of a gentleman who presented with features of Wernekink commissure syndrome and on evaluation was diagnosed to have multiple sclerosis. This is the first reported case of a patient with multiple sclerosis presenting with Wernekink commissure syndrome.